Quality of life in Croatian Homeland war (1991-1995) veterans who suffer from post-traumatic stress disorder and chronic pain - Braš, Marijana (BioMed Central, 2011)
BACKGROUND: The aim of this study was to investigate the quality of life in Croatian homeland war veterans who suffer from post-traumatic stress disorder and chronic low back pain (LBP). METHODS: A total of 369 participants were included, classified in four study groups: those with post-traumatic stress disorder (PTSD; N = 59), those with both PTSD and lower back pain (PTSD+LBP; N = 80), those with isolated LBP (N = 95) and controls (N = 135). WHOQOL-BREF survey was used in the estimation of quality of life. The data were analysed using statistical methods and hierarchical clustering. RESULTS: The results indicated a general pattern of lowering quality of life in participants with both psychological (PTSD) and physical (LBP) burden. The average overall quality of life was 2.82 ± 1.14 for the PTSD+LBP group, 3.29 ± 1.28 for the PTSD group, 4.04 ± 1.25 for the LBP group and 4.48 ± 0.80 for the controls (notably, all the pair-wise comparisons were significantly different at the level of P < 0.001, except for the pair LBP-controls, which was insignificant). This result indicated that quality of life was reduced for 9.9% in patients with LBP, 26.6% in patients with PTSD and 37.1% in PTSD+LBP, suggesting strong synergistic effect of PTSD and LBP. The analysis also identified several clusters of participants with different pattern of quality of life related outcomes, reflecting the complex nature of this indicator. CONCLUSIONS: The results of this study reiterate strong impact of PTSD on quality of life, which is additionally reduced if the patient also suffers from LBP. PTSD remains a substantial problem in Croatia, nearly two decades after the beginning of the 1991-1996 Homeland war.